PJMHS 2022
DOI: 10.53350/pjmhs221610193
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Admission Criteria and Academic Performance in Medical and Dental Colleges of Khyber Pakhtunkhwa

Abstract: Aim: To evaluate the connection among admission criteria and academic performance amongst medical and dental scholars of different institutes of Khyber Pakhtunkhwa. Study design: Quantitative-cross-sectional study. Study setting: Department of Medical Education of Khyber Medical University, Peshawar from 15th February to 15th July 2017. Methodology: Ten thousand and sixty one students attending 10 Medical colleges of KP from entering for qualification who were registered in the 2017, 2018, 2019, 2020, 2021 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Students qualifying for the merit are considered for admission. The effectiveness of this selection criterion also presents with contradictory results as prior studies from Pakistan have shown that admission tests and HSSC scores can be a reliable predictor of a student’s performance in the early years of medical school [ 11 , 12 ]. However, evidence of weaker correlations between the two is also available, along with recommendations to include non-cognitive assessments like interviews as admission prerequisites [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Students qualifying for the merit are considered for admission. The effectiveness of this selection criterion also presents with contradictory results as prior studies from Pakistan have shown that admission tests and HSSC scores can be a reliable predictor of a student’s performance in the early years of medical school [ 11 , 12 ]. However, evidence of weaker correlations between the two is also available, along with recommendations to include non-cognitive assessments like interviews as admission prerequisites [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%